Yasmin la amiga ebook - Aly, Hatem (Yasmin, 2020)
Yasmin sabe exactamente a qué quiere jugar cuando sus amigos vengan a su casa, pero ellos tienen otras ideas. ¿Podrán llegar a un acuerdo creativo que deje a todos contentos? Yasmin knows exactly what she wants to play when her friends come over. But it turns out her friends have their own ideas. Could a creative compromise make everyone happy?